Blended Learning Needs Analysis of Students in the SPOC Era: Local University Perspective in China - Lu, Lingming; Sitthiworachart, Jirarat; Petsangsri, Sirirat (My University, 2025)
With the development of the new generation of information technology, blended learning has entered the SPOC era, teachers and students can become the designers of the blended course. This also places higher demands on teachers and students' digital competence. Learning needs analysis is the most important step in SPOC-based blended learning. This article takes local university students in China as the survey object, and conducts a questionnaire survey on four aspects: individual learning aspirations, learning process needs, learning environment needs and learning ability gaps. The results show that today's university students have a strong willingness to blended learning, the demand for teaching resources is diversified, the learning process fails to fully give full play to the advantages of blended learning, the teaching evaluation needs to be reformed, and the gap between individuals is large. The study suggests that the current blended teaching should build high-quality learning resources, strengthen the interaction between online and offline teaching, pay more attention to the process and diversity evaluation of students.
Keywords: blended learning; learning needs analysis; online courses; SPOC era